The Role of Idealism and Relativism as Dispositional Characteristics in the Socially Responsible Decision-Making Process - Park, Haesun (Journal of business ethics, 2005)
This study investigated how decision-makers differ in processing their organizational environment (peers and organizational control systems), depending on the levels of their idealism and relativism. Focusing on socially responsible buying/sourcing issues, responses from buying/sourcing professionals from U.S. apparel and shoe companies were analyzed, using a series of regression analyses. The results generally supported the proposition that the degrees of idealism and relativism determine involvement levels that, in turn, result in varying levels of reactions to the organizational environment and corresponding amounts of information processing. Highly idealistic (relativistic) individuals were influenced by only idealistic (relativistic) signals of organizational environment. Further analysis showed highly idealistic and relativistic individuals were more likely to evaluate the organizational environment in terms of its business merit. The results suggest that organizations need to carefully plan how to communicate underlying meanings of organizational initiatives with their employees, knowing that individuals who have strong ethical opinions will only react to what they believe and elaborate its value for business. Further theoretical and practical implications and suggestions are discussed.